Mitral annular velocity measurement with cardiac magnetic resonance imaging using a novel annular tracking algorithm: Validation against echocardiography - Thavendiranathan, Paaladinesh; Guetter, Christoph; da Silveira, Juliana Serafim; Lu, Xiaoguang; Scandling, Debbie; Xue, Hui; Jolly, Marie-Pierre; Raman, Subha V.; Simonetti, Orlando P. (Magnetic resonance imaging, 2019)
Doppler based mitral annular velocities are an integral part of echocardiographic left ventricular diastolic function assessment. Although these measurements can be obtained by phase contrast cardiac magnetic resonance imaging (PC-CMR), this approach has limitations. The aims of this study were to assess the accuracy and reproducibility of a high temporal resolution steady-state free precession (SSFP) cine acquisition coupled with semi-automated mitral annular tracking to measure tissue velocity, and compare to echocardiography as the reference method. High temporal resolution (17 ms) 4-chamber cines were acquired in 25 volunteers using retrospective and prospective gating on a 3.0 T magnet. Mitral annular early (e′) and late (a′) tissue velocities were derived using a novel algorithm to semi-automatically detect the mitral valve insertion points and track its motion. Additionally, PC-CMR was used to measure mitral inflow early diastolic (E) velocity. Those measurements were also obtained using echocardiography based pulsed and tissue Doppler techniques, on the same day. Subjects were on average 34 ± 14 years-old (48% male). The lateral annulus e′ measurements had the best agreement with echocardiography with a concordance correlation coefficient (CCC) of 0.76 and 0.75 for prospectively and retrospectively gated cine CMR respectively. There was no significant difference in the lateral annular tissue velocities between echocardiography (13.8 ± 3.7 cm/s) and prospective (13.4 ± 3.7 cm/s) or retrospective (14.0 ± 3.7) acquisitions. Similarly, CMR measurement of E/e′ (a surrogate marker for LV filling pressures) using the lateral e′ velocity showed moderate agreement with echocardiography (CCC of 0.56 and 0.51 for prospective and retrospective acquisitions respectively) without a significant difference in ratios (5.3 ± 1.6 and 5.0 ± 1.3) compared to echocardiography (5.2 ± 1.4). Intra- and inter-observer reproducibility of the CMR-based annular velocity measurements was good. Measurements of mitral annular tissue velocities can be obtained from SSFP 4-chamber cine images using a semi-automated annular tracking algorithm, and demonstrates moderate agreement with echocardiography. The semi-automated method can provide quantitative mitral annular velocity measurements directly from conventional cine images, thereby providing additional clinically relevant information. The accuracy of this method in patients with diastolic dysfunction remains to be determined.